Dual Band High Efficiency Power Amplifier Based on CRLH Lines - Jimenez-Martin, J. L.; Gonzalez-Posadas, V.; Arques, F. J.; Garcia-Munoz, L. E.; Segovia-Vargas, D. (Společnost pro radioelektronické inženýrství, 2009)
In this paper we propose the use of Composite Right/Left Hand (CRLH) and Extended Composite Right/Left Hand (ECRLH) transmission lines for the design of dual band high efficiency power amplifiers working in CE class. The harmonic termination can be synthesized using the meta-lines is particularly suitable for CE class amplifiers, which have a termination not as sensitive to the third harmonic as F class amplifier. This paper presents the design procedure and the design equations. The nonlinear phase response of a CRLH and ECRLH transmission line has been utilized to design arbitrary dual-band amplifiers.
Keywords: eywords Power Amplifier; Meta-materials; CE class; CRLH; ECRLH; Diplexer; Statistical Sensitivity